Editorial: refractory GERD—good drug, wrong patients? Authors' reply. Issue 2 (15th June 2017) - Coyle, C.; Bytzer, P.
Abstract : Linked Content This article is linked to Katz and Coyle et al papers. To view these articles visithttps://doi.org/10.1111/apt.14120 andhttps://doi.org/10.1111/apt.14064 .